2005
DOI: 10.1002/cncr.20881
|View full text |Cite
|
Sign up to set email alerts
|

Thyroid hormone and breast carcinoma

Abstract: Background It has been a matter of controversy whether there is an increased risk of lung cancer among asbestos‐exposed workers without radiographic asbestosis. A previous study of lung cancer risk among asbestos‐cement workers has been updated with an additional 12 years of follow‐up. Methods Subjects had received radiographic examination at 20 and 25 years from first exposure to asbestos. Radiographs were interpreted by a single National Institute of Safety and Health (NIOSH)‐certified B‐reader using the 197… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
113
0
2

Year Published

2007
2007
2019
2019

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 187 publications
(120 citation statements)
references
References 20 publications
5
113
0
2
Order By: Relevance
“…Thyroid hormones may be permissive for tumor growth and may reduce survival in recurrent brain tumors (Hercbergs et al 2003) and in head and neck cancer (Nelson et al 2006). Moreover, a relationship between hypothyroidism and reduced incidence and less aggressiveness of breast cancer was demonstrated (Cristofanilli et al 2005). In 2007, Oetting Alexis demonstrated that thyroid hormones play important roles in proliferation and apoptosis (Oetting 2007).…”
Section: Hypothyroidism and Tumor's Outcomementioning
confidence: 99%
“…Thyroid hormones may be permissive for tumor growth and may reduce survival in recurrent brain tumors (Hercbergs et al 2003) and in head and neck cancer (Nelson et al 2006). Moreover, a relationship between hypothyroidism and reduced incidence and less aggressiveness of breast cancer was demonstrated (Cristofanilli et al 2005). In 2007, Oetting Alexis demonstrated that thyroid hormones play important roles in proliferation and apoptosis (Oetting 2007).…”
Section: Hypothyroidism and Tumor's Outcomementioning
confidence: 99%
“…Postmenopausal BC patients have been reported to have a significant increase in THs, suggesting that an imbalance between estradiol (E2) and T3 fosters the development of BC [44][45][46] . Conversely, hyperthyroidism has been associated with a reduction in the incidence of BC [47] . The literature describes an increase in survival in hyperthyroid patients with BC, suggesting that hyperthyroidism may protect against the development of BC by increasing steroid hormone binding globulin and by reducing estrogen stimulation of the breast tissue [48] .…”
Section: Resultsmentioning
confidence: 99%
“…A recently conducted meta-analysis found no statistically significant association between TH replacement and BC risk [19] . One of these studies demonstrated primary hyperthyroidism as a strong protective factor against BC after adjusting for clinical parameters including TH replacement therapy [47] . The literature contains a few studies that show a correlation between TH replacement therapy and BC, despite a tendency towards a non-statistical association between the two.…”
Section: Breast Cancermentioning
confidence: 99%
See 2 more Smart Citations